Research and application of single-cell sequencing in tumor heterogeneity and drug resistance of circulating tumor cells - Zhe Dai; Xu-yu Gu; Shou-yan Xiang; Dan-dan Gong; Chang-feng Man; Yu Fan (BMC, 2020)
Abstract Malignant tumor is a largely harmful disease worldwide. The cure rate of malignant tumors increases with the continuous discovery of anti-tumor drugs and the optimisation of chemotherapy options. However, drug resistance of tumor cells remains a massive obstacle in the treatment of anti-tumor drugs. The heterogeneity of malignant tumors makes studying it further difficult for us. In recent years, using single-cell sequencing technology to study and analyse circulating tumor cells can avoid the interference of tumor heterogeneity and provide a new perspective for us to understand tumor drug resistance.